A study on non-utilization of healthcare services among known diabetic and hypertensive patients at RHTC in Krishna district, Andhra Pradesh - Mendhe, Harshal; Makade, Kiran G.; Bhawnani, Dhiraj; N., Hanumanth; Singh, Daneshwar (International Journal Of Community Medicine And Public Health, 2017)
Background: Low uptake of health services for the management of hypertension and diabetes may reflect barriers related to individuals, health personnel, health systems, programs and health policies. Regularly on day to day basis, various services are available at the RHTC but it was found that less numbers diabetes and hypertensive patients are utilizing the health services at RHTC. With the above background the present study was planned and conducted to assess their health seeking behavior and to know the reasons of the non-utilization of health services at RHTC of Medical College. Methods: This community based descriptive study was conducted at RHTC of a Medical College in Krishna District of Andhra Pradesh. In depth interview was conducted for 508 known hypertensive and diabetic patients who were diagnosed at least one year back by physician and or on anti-diabetic or antihypertensive medications (self-reported) for more than one year. Results: 36% study participants were utilizing the services at RHTC. 21% study participants were utilizing services of Local RMP. 12% study participants were utilizing 104 services. 19% study participants said that RHTC was away from their home so they were not utilizing RHTC services. 28% agreed that doctors were inexperienced. 48% had opinion that prescribed drugs are costly. 21% said that transport facilities are not available. Conclusions: This study identified a wide range of barriers facing by patients pursing health services indicating the need for targeted multi-faceted interventions. To improve hypertension and diabetes control, intervention should overcome capability barriers, intension barriers and more specifically discussed health system barriers.